Microwave Assisted Synthesis of Molybdenum Disulphide/Tungsten Trioxide/Reduced Graphene Oxide (MoS2/WO3/RGO) Nanocomposites for Organic Vapor Sensing. Issue 1 (1st February 2022) - Gupta, Jyoti; Singhal, Prachi; Sunita Rattan, S
Abstract: Hybrid nanostructures based on two-dimensional (2-D) materials such as transition metal dichalcogenides (2-D TMD's), transition metal oxides (2-D TMO's), and graphene are gaining significant attention for their potential application as semiconductor sensing devices owing to their excellent structural, electronic, and optical characteristics. The present work reported 2-D ternary nanocomposites (MoS2/WO3/RGO) as organic vapor sensing material, synthesized using microwave assisted method. Formation of ternary composite system proves to be an efficient strategy to develop novel high performance vapour sensors, providing multiple degrees of freedom and opportunity to exploit the synergistic properties of the resulting material to its full potential for a particular application. The synthesized MoS2/WO3/RGO nanocomposites has been characterized for morphological, and structural analysis through SEM, XRD and FTIR spectroscopic techniques. The electrical and sensing studies of synthesized material is evaluated through IV characteristics using Keithley electrometer. The sensing characteristics has revealed that the synthesized sensor has high sensitivity, good stability at room temperature and outperforms the result obtained from single or binary counterparts. The formation of the heterojunction and electronic modulations at the interface of MoS2, WO3 and RGO results in improved surface charge transfer mechanism and enhancement of sensing performance.